'All of Ireland had been wiped out': Irish Nuclear Anxiety and Éilís Ní Dhuibhne's The Bray House. Issue 2 (November 2021) - Nolan, Val
Abstract : The Bray House (1990) is Éilís Ní Dhuibhne's curious and contested first novel, the story of a near-future archaeological expedition to an Ireland devastated by a British nuclear disaster. It is a book which has offered much analytical fodder to readers and critics alike, with the question of the novel's genre continually in flux since its publication. This article argues that, in The Bray House, Ní Dhuibhne consciously inverts Old Irish narrative forms to create a work of speculative writing which yokes together the seemingly contradictory concerns of the Gaelic literary tradition and contemporary Irish anxiety about vulnerabilities to the British nuclear energy industry. It examines how the author combines unease over international energy politics with native narrative structures to create a work which sits comfortably within the genre of science fiction. It considers how The Bray House brings to light what Darko Suvin calls the 'congeneric elements in the cognitive and marvellous bias of the voyage extraordinaire', in this case the Old Irish Echtra form. Particular attention is paid throughout to how science fiction (specifically the techno-Robinsonade model) allows Ní Dhuibhne to vividly express Irish national concerns over the presence of the Sellafield nuclear power plant in the late 1980s.